Giant schwannoma of the cheek – a comprehensive histological and immunohistochemical description of a rare tumour - Gajda, Mariusz; Zagólski, Olaf; Jasztal, Agnieszka; Lis, Grzegorz J.; Adamek, Dariusz; Litwin, Jan A. (Polish Journal of Pathology, 2009)
Schwannoma is a benign tumour originating from Schwann cells forming sheaths of peripheral nerves. Its location in the oral cavity, and particularly in the cheek, is very rare. A large tumour (5 cm) was surgically removed from the left cheek of a fifty-five-year-old man and pathological examination revealed schwannoma with Antoni A and B patterns. The tumour was investigated using immunofluorescence and histochemical stainings. It showed positive immunostaining for S-100, PGP 9.5, NSE, collagen IV, laminin, merosin and vimentin. No immunofluorescence for GFAP, NPY and CGRP was observed. Cells of the macrophage family (CD68-immunopositive) were scattered in the connective tissue. Neither B (CD20+) nor T (CD3+, CD8+) lymphocytes were found. The capillary network was revealed by CD34 immunostaining. SMA immunoreactivity was observed in walls of larger blood vessels but not in tumour cells. The tumour contained numerous mast cells visualized by thionin staining and an abundance of collagen fibres revealed by picrosirius red